Detection and Sequence Analysis of Grapevine Leafroll‐Associated Virus 2 Isolates from China. Issue 11 (15th May 2015) - Fan, Xudong; Dong, Yafeng; Zhang, Zun ping; Ren, Fang; Hu, Guojun; Zhou, Jun
Abstract: Several grapevine leafroll‐associated viruses (GLRaVs) have been found frequently in grapevines behaving GLD. Among them, GLRaV‐2 is the only one belonging to Closterovirus, and mainly induces leafroll symptoms and graft incompatibility. In this study, new degenerate primer pairs designed against the HSP70 gene were applied in polymerase chain reaction (PCR) and nested PCR (nPCR) to detect GLRaV‐2 in 132 samples collected from 14 provinces and regions of China. Of the samples, 51.5% were infected with GLRaV‐2, and most did not exhibit GLD symptoms. Some popular grape cultivars had a high incidence of GLRaV‐2 infection, such as Cabernet Sauvignon (92.3%), Chardonnay (80%), Red Globe (75%) and Italian Riesling (73.7%). 'Beta' rootstocks, previously identified as negative samples, were also found to be highly infected with GLRaV‐2 (50%). GLRaV‐2 isolates obtained in this study showed identities ranging from 68.9% to 100% and 76.47% to 100.0% at the nucleotide and amino acid levels, respectively. Phylogenetic analysis based on the HSP70 gene showed that all GLRaV‐2 isolates in China belong to three of five reported phylogenetic groups. Different variants belonging to the PN and RG groups were present in a single isolate. The results showed that the new degenerate primer pairs could detect more GLRaV‐2 isolates than the previously reported primers. This is the first detailed report on the prevalence and gene diversity of GLRaV‐2 in China and also provides an nPCR method to improve the sensitivity of PCR as an alternative method when no real‐time PCR device is available.